Phase transformations and subsurface changes in three dental zirconia grades after sandblasting with various al2 o3 particle sizes - Kim, Hee Kyung; Yoo, Kun Woo; Kim, Seung Joo; Jung, Chang Ho (Materials, 2021)
Although sandblasting is mainly used to improve bonding between dental zirconia and resin cement, the details on the in-depth damages are limited. The aim of this study was to evaluate phase transformations and subsurface changes after sandblasting in three different dental zirco-nia (3, 4, and 5 mol% yttria-stabilized zirconia; 3Y-TZP, 4Y-PSZ, and 5Y-PSZ). Zirconia specimens (14.0 × 14.0 × 1.0 mm3) were sandblasted using different alumina particle sizes (25, 50, 90, 110, and 125 µm) under 0.2 MPa for 10 s/cm2. Phase transformations and residual stresses were investigated using X-ray diffraction and the Williamson-Hall method. Subsurface damages were evaluated with cross-sections by a focused ion beam. Stress field during sandblasting was simulated by the finite element method. The subsurface changes after sandblasting were the emergence of a rhombohedral phase, micro/macro cracks, and compressive/tensile stresses depending on the interactions between blasting particles and zirconia substrates. 3Y-TZP blasted with 110-µm particles induced the deepest transformed layer with the largest compressive stress. The cracks propagated parallel to the surface with larger particles, being located up to 4.5 µm under the surface in 4Y-or 5Y-PSZ subgroups. The recommended sandblasting particles were 110 µm for 3Y-TZP and 50 µm for 4Y-PSZ or 5Y-PSZ for compressive stress-induced phase transformations without significant subsurface damages.
Keywords: Alumina particles; Resin cement; Rhombohedral phase; Stress field; Stress induced phase transformations; Sub-surface damage; Williamson-Hall; Zirconia substrates; Air abrasion; Dental stress analysis; Phase transition; Surface tension; Zirconium oxide